Preoperative plasmapheresis experience in Graves' disease patients with anti-thyroid drug-induced hepatotoxicity - YAVUZ, DİLEK (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Hepatotoxicity is a rare but serious side effect of antithyroid drug (ATI) therapy in Graves' disease patients. Cessation of ATI drug is needed in most of the patients if liver enzymes highly elevated or in case of agranulocytosis. Permanent therapy, surgery or radioactive iodine ablation are the treatment choices to ensure euthyroidism in active Graves' disease patients. Therapeutic plasma exchange (TPE) can be an option to ensure euthyroidism, especially in patients scheduled for urgent surgery. In the present study, we present consecutive five cases of methimazole related severe hepatotoxicity that underwent TPE before thyroid surgery. The median number of apheresis sessions was 3 (range: 2-5). Free triiodothyronine (FT3) 65-83 %, free thyroxine (FT4) 22-66 %, thyrotropin receptor antibodies (TRAB) 55-96 % decreases were observed. All patients underwent total thyroidectomy. TPE is an effective method to reduce serum FT3, FT4, TRAB levels in the short term to provide better thyroid hormone status before urgent surgery in ATI induced toxic hepatitis patients.
Keywords: Hepatitis; Methimazole; Plasmapheresis; Thyrotoxicosis; PLASMA-EXCHANGE; HEPATIC-INJURY; THYROID STORM; HYPERTHYROIDISM; THERAPY; THYROTOXICOSIS; METHIMAZOLE; GUIDELINES